2018
DOI: 10.1111/hir.12219
|View full text |Cite
|
Sign up to set email alerts
|

Localising and tailoring research evidence helps public health decision making

Abstract: Information professionals are instrumental in shaping what evidence enters local decision making processes. Identifying and supporting knowledge mobilisation roles within health libraries should be the focus of future research and training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…In another study data drawn from an NIHR-funded project examined how evidence is used in commissioning and planning, and also concluded the role of localised knowledge. They found that published evidence is "made fit" for local commission and planning by relating the evidence to local context and needs and tailored into local actionable messages [27].…”
Section: Considerations For Public Health Research Institutions and Fmentioning
confidence: 99%
“…In another study data drawn from an NIHR-funded project examined how evidence is used in commissioning and planning, and also concluded the role of localised knowledge. They found that published evidence is "made fit" for local commission and planning by relating the evidence to local context and needs and tailored into local actionable messages [27].…”
Section: Considerations For Public Health Research Institutions and Fmentioning
confidence: 99%
“…(3) Use an interactive team approach to data selection and extraction (4) Provide quantitative summary and qualitative thematic analysis in the report, as well as discussing implications for research and practice (5) Include consultations with stakeholders as mandatory knowledge translation component of scoping review…”
Section: Nonementioning
confidence: 99%
“…In addition to time constraints and accessibility, practitioners may lack the skills to nd, appraise and synthesise relevant evidence (3). The role of evidence-brie ng services and information professionals is to nd evidence relevant to local context and needs, and present them to commissioners as concise, actionable points (4,5). However, it is crucial that evidence guiding services and care provision comes from reliable sources, is critically appraised, and interpreted in the light of the overall body of available evidence (6).…”
Section: Introductionmentioning
confidence: 99%
“…A core component of a health library and information services is the provision of research evidence to inform decision making, and van der Graaf, Cheetham, Mccabe and Rushmer (2018) have been explored the mechanisms used to facilitate decision making in the planning of public health interventions. Data were drawn from 11 interviews, observations at meetings and documentary analysis.…”
Section: Evaluation and Impact Are Key Themes In This Issue Of The Hementioning
confidence: 99%